Kamus kedokteran Dorland W.A. Newman Dorland ; alih bahasa Huriawati Hartanto ; editor Lia Astika Sari, Sonta F. Manalu - DORLAND, W.A. Newman; Hartanto, Huriawati; Sari, Lia Astika; Manalu, Sonta F (EGC, 2002)
xxxi, 2549 hlm ilus 28 cm